2018
DOI: 10.1016/j.gaitpost.2018.06.113
|View full text |Cite
|
Sign up to set email alerts
|

Carrying asymmetric loads during stair negotiation: Loaded limb stance vs. unloaded limb stance

Abstract: General load carriage recommendations include carrying less than 20% BW loads and splitting loads bilaterally when feasible. Assessment recommendations include analyzing the first stair step and analyzing both the loaded and unloaded limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…Our hypothesis that hip abduction moments would incrementally increase with load in both stance phases of a step-up task was not supported. Contrary to our results, significant increases in hip abduction moments between no-load and +20% of BW have been quantified during the initial step up in adults (Wang and Gillette, 2018). Hip abductor muscle activations have also been shown to significantly increase between -30% of body weight and no-load during regular gait (Mun et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our hypothesis that hip abduction moments would incrementally increase with load in both stance phases of a step-up task was not supported. Contrary to our results, significant increases in hip abduction moments between no-load and +20% of BW have been quantified during the initial step up in adults (Wang and Gillette, 2018). Hip abductor muscle activations have also been shown to significantly increase between -30% of body weight and no-load during regular gait (Mun et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…The evidence is less robust for the effect of body weight modulation on the initiation of stair ascent. Researchers have postulated the importance of analyzing this specific movement because the first step up requires larger lower limb joint moments compared to subsequent steps (Wang and Gillette, 2018). This analysis may be especially important for pediatric clinical populations, for which a single step up can be a sensitive measure of movement quality (Stania et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that asymmetric load carriage resulted in significant differences in lower extremity joint moments between loaded and unloaded limbs during walking (DeVita et al, 1991;Matsuo et al, 2008) and stair negotiation (Wang and Gillette, 2018a). These differences are likely due to a larger moment arm from the load to the stance leg on the opposite side of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this analysis did not consider the substantial hip and knee flexion angles required to swing the limb onto the step or the extensor/adductor torque coupling that could explain decreases in hip abduction torque generation. Additionally, the authors focused on biomechanics of the second step, whereas the higher hip abduction moments required to transition from standing or level walking to stair ascent [17] make the first step likely more difficult post-stroke. These considerations may reveal the limits of lower extremity neuromuscular control.…”
Section: Introductionmentioning
confidence: 99%